Electronic and fluctuation dynamics following a quench to the superconducting phase - Stahl, Christopher; Eckstein, Martin (Physical Review B, 2021)
We investigate the dynamics of superconducting fluctuations in the attractive three-dimensional Hubbard model after a quench from the disordered phase to the ordered regime. While the long-time evolution is well understood in terms of dissipative time-dependent Ginzburg-Landau models with unstable potentials, early times are more demanding due to the inseparable dynamics of the pairing fluctuations and the electronic quasiparticles. Our simulation using the time-dependent fluctuation exchange approximation treats both degrees of freedom on the same footing and reveals a nonthermal electronic regime causing a nonmonotonous growth of the fluctuations. This feature is not directly captured by the Ginzburg-Landau theory but nevertheless remains observable beyond the thermalization time of the electrons. We further explore how the growth of the order parameter fluctuations leads to an opening of a pseudogap in the electronic spectrum and identify Andreev reflections as the dominant mechanism behind the gap opening.
CRIS-Team Scopus Importer:2021-02-12

Memory truncated Kadanoff-Baym equations - Stahl, Christopher; Dasari, Nagamalleswara Rao; Li, Jiajun; Picano, Antonio; Werner, Philipp; Eckstein, Martin (Physical Review B, 2022)
The Keldysh formalism for nonequilibrium Green's functions is a powerful theoretical framework for the description of the electronic structure, spectroscopy, and dynamics of strongly correlated systems. However, the underlying Kadanoff-Baym equations (KBE) for the two-time Keldysh Green's functions involve a memory kernel, which results in a high computational cost for long simulation times tmax, with a cubic scaling of the computation time with tmax. Truncation of the memory kernel can reduce the computational cost to linear scaling with tmax, but the required memory times will depend on the model and the diagrammatic approximation to the self-energy. We explain how a truncation of the memory kernel can be incorporated into the time-propagation algorithm to solve the KBE, and investigate the systematic truncation of the memory kernel for the Hubbard model in different parameter regimes, and for different diagrammatic approximations. The truncation is easier to control within dynamical mean-field solutions, where it is applied to a momentum-independent self-energy. Here, simulation times up to two orders of magnitude longer are accessible both in the weak and strong coupling regime, allowing for a study of long-time phenomena such as the crossover between prethermalization and thermalization dynamics.
CRIS-Team Scopus Importer:2022-04-22

Noise correlations in time- and angle-resolved photoemission spectroscopy - Stahl, Christopher; Eckstein, Martin (Physical Review B, 2019)
In time-resolved photoemission experiments, more than one electron can be emitted from the solid by a single ultrashort pulse. We theoretically demonstrate how correlations between the momenta of outgoing electrons relate to time-dependent two-particle correlations in the solid. This can extend the scope of time-and angle-resolved photoemission spectroscopy to probe superconducting and charge density fluctuations in systems without long-range order, and to reveal their dynamics independent of the electronic gap and thus unrestricted by the energy-time uncertainty. The proposal is illustrated for superconductivity in a BCS model. An impulsive perturbation can quench the gap on ultrafast timescales, while nonequilibrium pairing correlations persist much longer, even when electron-electron scattering beyond mean-field theory is taken into account. There is thus a clear distinction between a dephasing of the Cooper pairs and the thermalization into the normal state. While a measurement of the gap would be blind to such pairing correlations, they can be revealed by the angular correlations in photoemission.
CRIS-Team WoS Importer:2019-07-12